2010
DOI: 10.1152/ajpcell.00545.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ overload and mitochondrial permeability transition pore activation in living δ-sarcoglycan-deficient cardiomyocytes

Abstract: Muscular dystrophies are often associated with significant cardiac disease that can be the prominent feature associated with gene mutations in sarcoglycan. Cardiac cell death is a main feature of cardiomyopathy in sarcoglycan deficiency and may arise as a cardiomyocyte intrinsic process that remains unclear. Deficiency of delta-sarcoglycan (delta-SG) induces disruption of the dystrophin-associated glycoprotein complex, a known cause of membrane instability that may explain cardiomyocytes cytosolic Ca2+ increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Disruption of membrane stability by the loss of d-SG may lead to increased intracellular Ca 2 + levels that seem to be responsible for cell death (Fraysse et al, 2010). Previously, we have demonstrated that d-SG deficiency triggers a cascade of molecular modification in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of membrane stability by the loss of d-SG may lead to increased intracellular Ca 2 + levels that seem to be responsible for cell death (Fraysse et al, 2010). Previously, we have demonstrated that d-SG deficiency triggers a cascade of molecular modification in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…The precise pathophysiology of the cardiomyopathy remains largely unknown, but disruption of the DGC, due to a d-SG mutation, is the leading molecular event, which triggers the disease as it induces weakening of the mechanical connection between the contractile apparatus and the cell membrane. However, the membrane instability also allows increased entry of calcium via nonspecific channels and mitochondrial disorganization (Fraysse et al, 2010). Ample evidence suggests that abnormal elevation of cytosolic calcium may play a central role in the pathogenesis of heart disease (Dunn and Radda, 1991;Alloatti et al, 1995;Williams and Allen, 2007;Fauconnier et al, 2010;Sarma et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated cytosolic Ca 2ϩ , abnormal activity of the mitochondrial permeability transition pore, and necrosis is observed in ␦-sarcoglycan-deficient hamster cardiomyocytes (76). Analysis of Facio scapulo humeral dystrophy revealed decreased cytochrome c oxidase activity and reduced ATP synthesis (46) and altered mitochondrial permeability transition pore and apoptosis (77).…”
Section: Discussionmentioning
confidence: 99%
“…In the matrix, calcium upregulates the activity of Ca 2+ -sensitive dehydrogenases of the Krebs cycle and the F 1 F 0 -ATP synthase and thereby controls the rate of ATP production 5,6. A pathological aspect of this process is linked with the mitochondrial Ca 2+ overload, which might trigger the activation of the mitochondrial permeability transmission pore, which in turn releases apoptotic and necrotic signal factors, leading to cell death 7,8. Neuronal energy supplies are, meanwhile, entirely based on mitochondrial oxidative phosphorylation, making them especially vulnerable to mitochondrial dysfunction 4…”
Section: Introductionmentioning
confidence: 99%